Histological changes in the liver, kidney and spleen of White Albino Rat after Aluminum Chloride administration: Hadaf H. Mohammed1; Ibtisam K. Abd Ali2 and Ali F. Reshag1 - Mohammed, Hadaf H. (The Iraqi Journal of Veterinary Medicine, 2017)
The study was carried out to evaluate histological changes induced by Aluminum chloride in Wistar rats. Forty rats were uniformly divided into two different groups: The control group were given distilled water during period of experiment and the first group were given oral daily dose of Aluminium chloride (37 mgB.W). After 60 days of treatment rats were sacrificed. Liver, kidney and spleen were processed and stained with Haematoxylin and Eosin the lesions of these organs were characterized by degeneration, necrosis, and congestion which meant that Aluminum chloride was nephrotoxic as well as hepatotoxic in nature. Microscopic examination results showed that Aluminum chloride exposure was harmful to the histological structure of liver, kidney and spleen.